PREFACE - Bernardo-Filho, Mario (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
PrefaceComprehension of the health-disease relationship and its consequences require that health professionals should continuously update their knowledge. Incorporation of procedures involving technologies in healthcare is highly desirable to increase scientific evidence about the effectiveness and practice of therapeutics. The use of these technologies should also be related to health promotion and quality of life improvement. Exchanging and sharing of scientific information to facilitate critical evaluation of techniques used clinically is essential.Some interventions available in healthcare are often not widely used. Although the Traditional Chinese Medicine TCM) practices are known to be ancient, some of them had only recently increased their acceptability as clinical procedures in many countries from the publication of the “Strategic Plan for Traditional Medicine 2002-2005” (published by the World Health Organization in 2002). Several interventions of the TCM are included among the Traditional, Complementary and Alternative Medicines (TCAM).A shared point of the TCAM is the emphasis on friendly conduct in the development of the therapeutic relationship, and the integration of human beings with their environment and society. Following this concept, it is possible to suggest that the use of oscillating/vibratory platform that produces mechanical vibration, and can generate whole body vibration exercise (WBVE), as an additional complementary and alternative medicine (CAM).WBVE would be an alternative remedy to improve clinical and functional aspects, and to enhance physical capability. However, it is still timidly used by some health professionals. It is necessary to take caution in the exposition of a person, healthy or not, trained or not, to WBVE. Well-defined criteria must be followed, guided by prescription of insurance parameters in order to result in desirable physiological/clinical effects. Biomechanical parameters of the mechanical vibration must be considered, such as (i) frequency, (ii) peak-to-peak displacement, (iii) exposure time, (iv) rest time, and (v) position of the individual on the base of the platform must be well established.The holistic view of the processes involved in health-disease relationship, health promotion and quality of life improvement, are closely related. This raises guided approaches in TCAM and WBVE applied in various special populations seeking health promotion and improvement of physical fitness.Putting together all these considerations, “The First International Congress on Mechanical Vibrations and on Integrative and Complementary Practices”, held in 2016, at Cabo Frio, Rio de Janeiro, Brazil, was an opportunity to meet the professionals who work with the implementation of these TCAM interventions, and with the investigations on these techniques.Considering all challenges associated with the organization of an International Congress, we decided to organize an international forum for debate about the proposed theme, and to publish the findings of the Congress in a special issue of the African Journal of Traditional, Complementary and Alternative Medicines. This process will, hopefully, encourage further research, basic and applied, in the area, and thus enhance the scientific evidence, and the dissemination of knowledge about the benefits, and the care necessary for proper and safer use of TCAM.Mario Bernardo-Filho, PhDGuest Editor.